The Effect of Using the Baamboozle Game on the Civic Education Learning Outcomes of Third-Grade Students at MI Sirojul Anwar - Adinda Nur Alfia Azzahra; Khaidir Fadil Fadil; Mukhrij Sidqy (Jurnal Evaluasi dan Pembelajaran, 2026)
This study aims to determine the effect of using the Baamboozle game on the Civic Education learning outcomes of third-grade students at MI Sirojul Anwar. The research method used was a quasi-experimental study with a Non-Equivalent Control-Group Design. The research sample consisted of 60 students divided into an experimental class (30 students) and a control class (30 students). The research instrument was an essay test consisting of 20 questions, the validity of which was tested using the Product Moment correlation with a table r value of 0.361, resulting in 15 valid questions and 5 invalid questions. The reliability test using Cronbach’s Alpha yielded a value of 0.858, which falls into the very high category. Data analysis techniques included the Shapiro-Wilk normality test, Levene’s Test for homogeneity, Paired Sample T-Test, and Independent Sample T-Test using SPSS 23. The results showed that the experimental class’s pretest average of 28.13 increased to 38.66 on the posttest, representing a 36.95% increase or a rise of 10.53 points. The control class increased from 27.66 to 32.86, representing an 18.75% increase or a rise of 5.20 points. Based on the Independent Sample T-Test, a significance value of 0.000 < 0.05 was obtained, indicating a significant effect of the use of the Baamboozle game on students’ Civic Education learning outcomes. It can be concluded that the Baamboozle game is effective in improving Civic Education learning outcomes.